Implementation of the Law on Halal Product Guarantees on Halal Labeling in Food Stalls in North Kolaka district (Maqasid Al-Syariah Analysis) - Nirwana Miswar (International Journal of Islamic Studies, 2024)
The main problem of this research is how to analyze the law on halal product guarantees regarding the giving of halal labels to food stalls in North Kolaka district? The subject matter is then broken down into several sub-problems or research questions, namely: 1) what is the general description of food stalls in North Kolaka Regency 2) What is the policy of the Ministry of Religion of North Kolaka Regency regarding the Implementation of the Law on Halal Product Guarantees in Assigning Halal Labels to Food Stalls in North Kolaka Regency? 3) How is the implementation of the law on halal product guarantees regarding the provision of halal labels to food stalls in North Kolaka district? 4) What is the maqasid al-shariah analysis of halal labeling in restaurants in North Kolaka district? This type of research is classified as qualitative with the research approach used is a juridical approach, a syar'i approach, and a sociological approach. The data source for this research is a data source in the form of humans in research in general as respondents. Furthermore, the data collection methods used were observation, interviews, documentation, and reference tracing. Then, data processing techniques and data analysis were carried out through several stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that 1) Food stalls in North Kolaka Regency are business opportunities that have continued to develop in accordance with increasingly advanced times 2) The policy of the Ministry of Religion of North Kolaka Regency regarding the implementation of the law on halal product guarantees regarding the provision of halal labels to food stalls in North Kolaka Regency is currently still not optimal. The constraints faced as UUJPH implementers. First, the draft implementing regulations for the JPH Law were purely the result of the Ministry of Religion without any bilateral relations between other ministries in their fields. Second, when the draft was rejected by the PAK, the Ministry of Religion had to start all over again to make the draft. Third, during the meeting to discuss the draft implementing regulations for the JPH Law with the PAK who were present were not the heads of ministry policies in their fields. 3) The method of implementing Law Number 33 of 2014 concerning Guaranteed Halal Products has not gone well because the average restaurant in North Kolaka Regency has not been labeled halal. As for the factors hindering this implementation, namely the participation of law enforcement officials has not been running as it should, then the public's attitude towards the existence of this law does not seem to care too much. 4) Analysis of Maqāṣid asy-syarīʻah on giving halal labels to restaurants in the first Kolaka Regency, the JPH Law can provide comfort, security, safety, and certainty of the availability of Halal Products for the community with the aim of implementing guarantees to increase halal products. Second, the Halal JPH Law can provide added value for business actors to produce and sell Halal Products.